Single-phase La0.8Sr0.2Co1-xMnxO3-δ electrocatalyst as a triple H+/O2-/e- conductor enabling high-performance intermediate-temperature water electrolysis - Ning Wang; Chunmei Tang; Lei Du; Zhao-Qing Liu; Weiyan Li; Zhongqian Song; Yoshitaka Aoki; Siyu Ye (Journal of Materiomics, 2022)
Hydrogen, especially the “green hydrogen” based on water electrolysis, is of great importance to build a sustainable society due to its high-energy-density, zero-carbon-emission features, and wide-range applications. Today's water electrolysis is usually carried out in either low-temperature (<100 °C), e.g., alkaline electrolyzer, or high-temperature (>700 °C) applications, e.g., solid oxide electrolyzer. However, the low-temperature devices usually suffer from high applied voltages (usually >1.5 V @0.01 A cm−2) and high cost; meanwhile, the high-temperature ones have an unsatisfied lifetime partially due to the incompatibility among components. Reasonably, an intermediate-temperature device, namely, proton ceramic cell (PCC), has been recently proposed. The widely-used air electrode for PCC is based on double O2-/e- conductor or composited O2-/e-−H+ conductor, limiting the accessible reaction region. Herein, we designed a single-phase La0.8Sr0.2Co1-xMnxO3-δ (LSCM) with triple H+/O2-/e- conductivity as the air electrode for PCCs. Specifically, the La0.8Sr0.2Co0.8Mn0.2O3-δ (LSCM8282) incorporates 5.8% proton carriers in molar fraction at 400 °C, indicating superior proton conducting ability. Impressively, a high current density of 1580 mA cm−2 for hydrogen production (water electrolysis) is achieved at 1.3 V and 650 °C, surpassing most low- and high-temperature devices reported so far. Meanwhile, such a PCC can also be operated under a reversible fuel cell mode, with a peak power density of 521 mW cm−2 at 650 °C. By correlating the electrochemical performances with the hydrated proton concentration of single-phase triple conducting air electrodes in this work and our previous work, a principle for rational design of high-performance PCCs is proposed.